2014
DOI: 10.1096/fj.14-255240
|View full text |Cite
|
Sign up to set email alerts
|

Impact on offspring methylation patterns of maternal gestational diabetes mellitus and intrauterine growth restraint suggest common genes and pathways linked to subsequent type 2 diabetes risk

Abstract: Size at birth, postnatal weight gain, and adult risk for type 2 diabetes may reflect environmental exposures during developmental plasticity and may be mediated by epigenetics. Both low birth weight (BW), as a marker of fetal growth restraint, and high birth weight (BW), especially after gestational diabetes mellitus (GDM), have been linked to increased risk of adult type 2 diabetes. We assessed DNA methylation patterns using a bead chip in cord blood samples from infants of mothers with GDM (group 1) and infa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
79
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 50 publications
2
79
0
Order By: Relevance
“…A number of studies have shown that the maternal environment, in particular hyperglycaemia during pregnancy, can alter foetal development, affecting organ formation and increasing the risk of diseases such as neural tube defects, cardiovascular disease, obesity, diabetes, and cancer in the offspring via epigenetic mechanisms313233343536373839. In the present study, we established a maternal gestational diabetes rat model to determine its effects on tooth development in offspring and to study the mechanisms associated with these effects.…”
Section: Discussionmentioning
confidence: 95%
“…A number of studies have shown that the maternal environment, in particular hyperglycaemia during pregnancy, can alter foetal development, affecting organ formation and increasing the risk of diseases such as neural tube defects, cardiovascular disease, obesity, diabetes, and cancer in the offspring via epigenetic mechanisms313233343536373839. In the present study, we established a maternal gestational diabetes rat model to determine its effects on tooth development in offspring and to study the mechanisms associated with these effects.…”
Section: Discussionmentioning
confidence: 95%
“…Targeted and global epigenetic changes, including changes in methylation of genes encoding adipokines, have been reported in placenta (a central organ in the flux of nutrition from mother to fetus, important for mediating the impact of maternal GDM) and cord blood from newborn offspring in response to prenatal exposure to maternal obesity, hyperglycemia, and GDM [1627], but the extent to which these changes persist into adulthood is unknown. Studies of the association between maternal glycemia or BMI and offspring adipokine methylation have rendered contradictory results, showing decreased LEP and ADIPOQ methylation on the fetal side of the placenta with increasing maternal blood glucose concentrations [17, 18] or increased placental LEP DNA methylation with exposure to gestational diabetes mellitus (GDM) and maternal obesity [23].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several studies have demonstrated alteration of DNA methylation patterns in offspring of diabetic mothers1520, but to the best of our knowledge, we are the first to show that maternal diabetes may modify the association between intrauterine growth restriction and adult-onset diabetes in a sex-specific manner. DNA methylation of loci associated with insulin resistance and type 2 diabetes in infants born to mothers with gestational diabetes and in infants born with growth restriction demonstrates large changes in methylation but surprisingly little overlap in specific methylated loci by sex47. The fact that we only found that low birth weight men with maternal history of diabetes have increased risk of diabetes suggest factors leading to low birth weight in men other than maternal diabetes are not sufficient to confer diabetes risk.…”
Section: Discussionmentioning
confidence: 54%